The Comparision of Social Anxiety Disorder and Shyness in Addicted and Non-Addicted Men - Anari; Shafiee Tabar; Pouretemad (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: The aim of this study was to compare social anxiety disorder and shyness in addicted and non-addicted men. Method: The method of this study was causal-comparative research and the sampling done by purposive sampling. However, 30 men who were addicted to opium and were referred for the first time to Arak Behzisti self report center were selected. Then, 30 paired samples of non-addicted men who had not any addiction history in their life selected as a comparison group and Henderson/Zimbardo Shyness Questionnaire (2001) and Liebowitz Social Anxiety Scale (1981) were administered in both groups. In SPSS software data was analyzed by running of independent samples t test. Results: the results showed that addicted men had reported higher scores in shyness and social phobia disorder in comparison to non-addicted men. Conclusion: With consideration of results it can be concluded that people with shyness and social anxiety disorder, use opium to reduce social anxiety and avoidance. Clinical implications for the prevention and treatment of substance abuse should be considered.